Interior Modification of Residential Housing in Flood Prone Areas - Hidayati, Zakiah; Noviana, Mafazah; Rosyidi, Muhammad Fadzillah (TDMRC, Universitas Syiah Kuala, 2022)
For over two decades (1998, 2008, 2019), floods have occurred in Samarinda in various intensities and different areas. In Bengkuring, flooding has submerged houses for days since 2008. It happens for days with an average depth of 0.5-1 meter. Flooding can cause minor, moderate, and severe damage or destruction of homes, property, and community disorders. People whose homes are submerged by floods make some adaptations to mitigate. Some modifications are to create a small barrier in front of the house, raise the floor, and repair waterways. Safe space is crucial during floods, especially in a one-story house. This study aims to improve the form of adaptation in residential homes in flood-prone areas. Similarly, the objective is to modify the interior to create a safe space for goods and occupants. The method of data analysis is based on Space Syntax Analysis J-Graphs. Occasionally, J-Graphs can efficiently explain interior modifications, including the ratio and layer of safe spaces, the number of indoor and outdoor connecting rooms, and the ring configuration. Through the design approach and prototype demonstration, it is possible to install interior modifications by making mezzanine floors and utilizing the attic. Although most previous research on building adaptation focused on home construction, home interior modification promises advantages that will result in a more straightforward and workable project for the community's needs.